THE EFFECTS OF EARLY AND LATE INTERMITTENT FASTING ON THE INFLAMMATION IN MEN AND WOMEN - Zhorabek, Iliyas (Nazarbayev University School of Medicine, 2024)
Although studies show the effectiveness of time-restricted feeding (TRF) regimen for weight loss, there is limited data to suggest if an early or late eating window is more effective. The objective of this case-crossover study was to compare the effects of early TRF and late TRF on body parameters, lipid profile, and inflammatory markers. Young, healthy individuals with body mass index (BMI) no more than 29.9 were recruited. They were randomly assigned into two groups, which practiced TRF for 4 weeks starting with either an early or late eating window. After 4 weeks, the participants returned to their regular eating time for two weeks, after which they switched their eating time. Body measurements and blood tests for lipid profile and inflammatory markers were conducted before and after each fasting period. 44 participants were recruited and divided in a 1:1 ratio into two groups. Early TRF regimen was shown to be more effective in lowering BMI compared to late TRF, with mean difference in change of 0.484±0.60 kg/m2 (p-value < 0.05). There was no statistically significant difference in changes in total cholesterol, LDL, HDL, triglycerides, CRP, and homocysteine. The results of this study suggest that early TRF regimen is more effective for weight-loss than late TRF, while the lipid profile and inflammatory markers are not significantly affected.
Keywords: type of access: gated access